The ethical governance of end–of-life care: the quest for an integrated juridical framework - Haneef, Sayed Sikandar Shah; Mat Jubri@Shamsuddin, Mustafa (2017)
Unprecedented advancement in medical technology and its rapidly growing field of allied sciences indisputably have contributed significantly to the treatment of diseases and even inborn defects. Meanwhile it has challenged many traditional socio-cultural constructs about diseases, natural deformities and even “life” and “death”, and continues to do so unabatedly. As to how Muslims should approach such novelties on their own terms, Maqasid al-Shari`ah aside from classical usul methodology and theological constructs are some of the deliberated moral frameworks suggested as the most appropriate launching paths. The proponents of each advocacy while conceding the merits of other alternative paradigms believe in the moral superiority of their projects, without sufficiently delineating them. This study, therefore, will present a compact critiques of the above with the purpose of outlining the traits for an integrated juridical framework to address the issue of the end-of -life care.